Strategies and factors associated with preparing for competing in the heat: a cohort study at the 2015 IAAF World Athletics Championships. Issue 4 (4th November 2016) - Périard, Julien D; Racinais, Sébastien; Timpka, Toomas; Dahlström, Örjan; Spreco, Armin; Jacobsson, Jenny; Bargoria, Victor; Halje, Karin; Alonso, Juan-Manuel
Abstract : Purpose: Assess exertional heat illness (EHI) history and preparedness in athletes competing in a World Athletics Championships under hot/humid conditions and identify the factors associated with preparedness strategies. Methods: Of the 207 registered national teams invited to participate in the study, 50 (24%) accepted. The 957 athletes (49% of all 1965 registered) in these teams were invited to complete a precompetition questionnaire evaluating EHI history, heat stress prevention (heat acclimatisation, precooling and hydration) and recovery. Responses from 307 (32%) athletes were separated in field events, sprints, middle-distance and long-distance running, and decathlon/heptathlon for analysis. Results: 48% of athletes had previously experienced EHI symptoms and 8.5% had been diagnosed with EHI. 15% heat acclimatised (∼20 days) before the championships. 52% had a precooling strategy, ice slurry ingestion (24%) being the most prevalent and women using it more frequently than men (p=0.005). 96% of athletes had a fluid consumption strategy, which differed between event categories (p<0.001). The most common volumes planned on being consumed were 0.5–1 L (27.2%) and ≥2 L (21.8%), water being the most frequent. 89% of athletes planned on using at least one recovery strategy. Female sex (p=0.024) and a previous EHI diagnosis increased the likelihood of using all 3 prevention strategies (p<0.001). Conclusions: At a World Championships with expected hot/humid conditions, less than one-fifth of athletes heat acclimatised, half had a precooling strategy and almost all a hydration plan. Women, and especially athletes with an EHI history, were more predisposed to use a complete heat stress prevention strategy. More information regarding heat acclimatisation should be provided to protect athlete health and optimise performance at major athletics competitions in the heat.